Bingo and Brains: Gamifying Vocabulary Learning in an Islamic High School Setting - Taufik Hidayah; Siti Al-mar’atus Sholehah (ELLITE: Journal of English Language, Literature, and Teaching, 2026)
Vocabulary mastery plays a vital role in supporting English language proficiency, particularly for learners in English as a Foreign Language (EFL) contexts. This research was conducted due to the importance of vocabulary mastery in supporting students' English language skills. It investigates the effectiveness of the Word Bingo game in enhancing the vocabulary mastery of tenth-grade students at an Islamic upper secondary school in Jember, Indonesia. A quantitative approach using a quasi-experimental design with a non-equivalent control group is employed in this study. The sample consisted of 48 tenth grade students divided into an experimental class and a control class. The data were collected through pre-tests and post-tests and then analyzed using statistical tests such as normality, homogeneity, and independent sample t-tests. The findings showed a significant improvement in the vocabulary mastery of students who were taught using the Word Bingo Game compared to those who received conventional instruction. Based on the results, it can be concluded that the Word Bingo Game is an effective method to enhance vocabulary mastery among tenth grade students. It not only increases student motivation and engagement but also improves their ability to recall and apply new vocabulary in learning activities.